Molecularly imprinted polymer/CdTe quantum dots-decorated polymer optic fiber microprobes for Amoxicillin detection - Liang, Jianfeng; Wu, Qixuan; Xiao, Ran; Yu, Ruijie; Chen, Hao; Tang, Yangjie; Zhang, Jie; Liu, Chenchen; Yang, Guowei; Lei, Hongxiang (Frontiers in Bioengineering and Biotechnology, 2025)
Amoxicillin (AMX) is a widely used antibiotic for infectious diseases. However, excessive residues of AMX in the food chain and environment pose serious threats to public health, making precise monitoring of AMX crucial. Among various detection methods, fluorescence spectroscopy has garnered significant attention due to its unique advantages. Nevertheless, conventional fluorescence probes based on organic dyes or quantum dots (QDs) suffer from limitations such as difficult separation, easy pollution, poor biocompatibility and safety, lack of specificity and in situ detection. To address these challenges, we developed a novel sensor based on a molecularly imprinted polymer (MIP)/CdTe quantum dots-decorated polymer optical fiber microprobe (POF MP) for AMX detection. This sensor offers multiple advantages, including good specificity, reusability and stability, excellent biocompatibility and safety, in situ monitoring, and residue-free operation. The proposed sensor demonstrates a linear detection range of 0.5–50 μg/L with a limit of detection (LOD) of 0.31 μg/L. This innovative sensor provides a promising solution for monitoring AMX concentrations in biological and environmental systems, contributing to advancements in microenvironmental monitoring, pharmaceutical sensing, and biomedical therapeutics.